Effectiveness of mindfulness and Qigong training for self-healing in patients with Hwabyung and depressive disorder: a protocol for a randomized controlled trial - Yoon, Seok-In; Park, Hui-Yeong; Lee, Hyun Woo; Park, Chan; Chung, Sun-Yong; Kim, Jong Woo (Frontiers in Psychiatry, 2024)
Background: Hwabyung is a Korean culture-bound syndrome characterized by anger-related physical and psychological symptoms. Depressive disorder is a common mental illness occurring worldwide, and has been reported to have a high comorbidity rate with Hwabyung. For patients with depressive disorders, differential diagnosis and combined treatment for Hwabyung should be considered. Mindfulness and Qigong may be effective alternatives for regulating emotions such as depression, anxiety, and anger. This study aims to investigate whether Mindfulness and Qigong Training for Self-Healing (MQT-SH) would improve emotional problems in patients with Hwabyung and depressive disorder. Methods: This study will be a two-arm block randomized controlled trial. A total of 64 participants will be recruited and randomly assigned to either experimental or control group. While the experimental group will perform MQT-SH for the first six weeks, the control group will receive no treatment. During the next six weeks, the control group will perform MQT-SH for ethical equity. Assessments will be conducted at baseline, post-intervention (6 weeks) and follow-up (12 weeks). The primary outcomes would be Hwabyung and depression, while the secondary outcomes would include anxiety, anger, and vitality. Discussion: This study will provide a basis for assessing the effectiveness of mindfulness and Qigong training in patients with Hwabyung and depressive disorder. Ethics and dissemination: This study was approved by the Institutional Review Board of Kyung-Hee University Oriental Medicine Hospital in Gangdong (KHNMCOH 2023-09-003). The results will be disseminated through peer-reviewed publications. Trial registration: This trial was registered with the Clinical Research Information Service (CRIS), Republic of Korea, No. KCT0008937 and was registered on November 10, 2023.